Real Time Emotion Detection and Sentiment Recognition - Mrs. Jaya Dewan, Pratik Gadge, Kapil More, Pooja Bhosale; Shivani Borkar (International Journal of Advanced Science and Technology, 2020)
According to the present scenario, depression is one of the serious problems in the society. Although mental health issues like depression and stress are having cures, but they are not treated as serious as other physical disorders or problems. Many times, the main cause of emotional issues or depressed mood are the unspoken problems in life. One may find a small problem as a huge barrier in life by overthinking about it. As a cure, people around the depressed person can help by creating a positive environment or atmosphere around him. But nowadays people often tend not to share their personal issues with anyone and avoid to have conversations regarding the problems in life. Also, people rely so much on technology and try to share their emotions through various technological platforms like social media than to share it with someone directly. The motive of this project is to understand the emotion of the user while having a real time conversation (speech or text) with the system and reply with appropriate positive feedback to create a positive atmosphere around him, depending on the emotion and current mental state of user and also recommend a video as per the emotion class and the conversational analysis of user.